2017
DOI: 10.1104/pp.17.00495
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Pumps and Interacting BON1 Protein Modulate Calcium Signature, Stomatal Closure, and Plant Immunity

Abstract: Calcium signaling is essential for environmental responses including immune responses. Here, we provide evidence that the evolutionarily conserved protein BONZAI1 (BON1) functions together with autoinhibited calcium ATPase10 (ACA10) and ACA8 to regulate calcium signals in Arabidopsis. BON1 is a plasma membrane localized protein that negatively regulates the expression of immune receptor genes and positively regulates stomatal closure. We found that BON1 interacts with the autoinhibitory domains of ACA10 and AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 68 publications
3
59
0
Order By: Relevance
“…Another study by Frei dit Frey et al (2012) revealed that ACA8 and ACA10 interact with membrane-resident receptor kinases and represent an important component of receptor-mediated signalling in plant immune responses and development. These findings were recently confirmed by Yang et al (2017), who showed that the evolutionarily conserved protein BONZAI1 interacts with ACA10 and ACA8 to function in the generation of cytosolic calcium signatures that are critical for stomatal movement and associated plant immunity. Finally, various ACA and ACA isoforms were shown to be central to plant adaptive responses to a broad range of abiotic stresses (see Table S1).…”
Section: New Phytologistmentioning
confidence: 66%
See 1 more Smart Citation
“…Another study by Frei dit Frey et al (2012) revealed that ACA8 and ACA10 interact with membrane-resident receptor kinases and represent an important component of receptor-mediated signalling in plant immune responses and development. These findings were recently confirmed by Yang et al (2017), who showed that the evolutionarily conserved protein BONZAI1 interacts with ACA10 and ACA8 to function in the generation of cytosolic calcium signatures that are critical for stomatal movement and associated plant immunity. Finally, various ACA and ACA isoforms were shown to be central to plant adaptive responses to a broad range of abiotic stresses (see Table S1).…”
Section: New Phytologistmentioning
confidence: 66%
“…These findings were recently confirmed by Yang et al . (), who showed that the evolutionarily conserved protein BONZAI1 interacts with ACA10 and ACA8 to function in the generation of cytosolic calcium signatures that are critical for stomatal movement and associated plant immunity. Finally, various ACA and ACA isoforms were shown to be central to plant adaptive responses to a broad range of abiotic stresses (see Table S1).…”
Section: Ca2+ Extrusion Systemsmentioning
confidence: 99%
“…HMA1) and Ca 2+ exchangers (CAX) represent the known efflux or 'off' components of the Ca 2+ machinery (Moreno et al, 2008;Bose et al, 2011;Manohar et al, 2011;Pittman, 2011;Spalding & Harper, 2011). Such a signatureshaping function of Ca 2+ transporters was recently exemplified by studies on the function and Ca 2+ -dependent phosphorylation mediated regulation of ACA8 (Costa et al, 2017;Yang et al, 2017).…”
Section: Ca 2+ Importer and Exporter In Plantsmentioning
confidence: 99%
“…The calcium influxes and activation of MAPK cascades after recognition of ligands by PRRs promote stomatal closure that limits entry of bacterial pathogens into leaves (Couto and Zipfel 2016; Tang et al 2017). For example, the PM‐localized protein BONZAI1 (BON1) positively regulates the stomatal closure by interacting with and activating the calcium pumps AUTOINHIBITED CALCIUM ATPASE 10 (ACA10) and ACA8 followed by the change of [Ca 2+ ] cyt concentration and calcium signals (Yang et al 2017). The MAMP‐induced stomatal closure is abolished in mutants that loss of function of MPK3/6 or their upstream MKK4/5 independently of abscisic acid (ABA) signaling (Su et al 2017).…”
Section: Recent Discoveries Of the Activation Of Immunity Mediated Bymentioning
confidence: 99%